A comprehensive survey of both RHD and RHCE allele frequencies in sub‐Saharan Africa. Issue 11 (29th August 2013) - Granier, Thomas; Beley, Sophie; Chiaroni, Jacques; Bailly, Pascal; Silvy, Monique
Abstract : Background: The RH system is one of the most polymorphic blood group systems with numerous allele variants affecting Rh polypeptides expression. This complexity is at the origin of difficulties for transfusion of African patients especially sickle cell disease patients requiring chronic transfusion therapy with high risk of immunization. As a complete survey of RH variants is lacking in African populations, we performed red blood cell genotyping to determine the type and frequency of RHD and RHCE alleles in sub‐Saharan African populations. Study Design and Methods: A total of 347 blood samples were collected from individuals of six nonpygmoid and three pygmoid populations. RH typing was performed using two single‐tube multiplex polymerase chain reaction amplifications (BioArray Solutions, Immucor). Results: All six sub‐Saharan nonpygmoid populations exhibited constant variety in both type and frequency of aberrant RHD and RHCE alleles. Predicted partial RH1 (1.8%) and RH5 (0.9%) phenotypes were less than expected. Conversely, predicted partial phenotype RH2 (5.5%) was frequent. Data confirmed the high frequency of samples positive for the non–clinically significant RH10/RH20 antigens (39.5%) and revealed a high frequency of RH54 (DAK, 8.1%). The pygmoid groups showed higher percentages of predicted partial RH antigens and greater heterogeneity reflecting wide genetic differentiation. Conclusion: Our data show that frequencies of aberrant RHD and RHCE alleles were similar, irrespective of location and ethnicity. In view of the predicted frequencies and relative clinical significance of both private antigens and high‐prevalence antigens absent, the most relevant assays for individuals of African descent in a transfusion setting are for 1) partial RH2 in the patient and 2) RH54 (DAK) in the donor.